UJI AKTIVITAS ANTIHIPERKOLESTEROLEMIA EKSTRAK AIR BUAH BELIMBING WULUH (Averrhoa bilimbi Linn.) PADA PEMODELAN TIKUS JANTAN GALUR WISTAR HIPERKOLESTEROLEMIA - Bary Azhari; Sri Luliana; Robiyanto Robiyanto (Majalah Obat Tradisional, 2017)
Belimbing wuluh (Averrhoa bilimbi Linn.) has antihypercholesterolemic activity. This study aims to determine antihypercholesterolemic potential, optimal dosage and effect of water extracts of Belimbing wuluh (Averrhoa bilimbi Linn) on the index of rat organs. Test animals used were male Wistar rats, divided into 4 groups: normal control, negative control, positive conrol (simvastatin 0.18 mg/kg), and the aqueous extracts of fruit Belimbing wuluh dose of 63 mg/kg. The parameter which was measured in this study were total cholesterol levels which obtained using CHOD-PAP method, the weight of rats for 50 days, and organ indexes. Those parameters were further tested with One Way ANOVA. In parameter decrease blood cholesterol levels of rats between groups positive and group aqueous extract of the fruit starfruit  dose of 63 mg/kg did not experience a statistically significant difference. Meanwhile, the group aqueous extract of the fruit starfruit dose 63 mg/kg and a negative control experiencing significant difference (p<0.05). Conclusion, aqueous extract of the fruit starfruit dose of 63 mg/kg had the effect antihypercholesterolemic seen from the decrease in total cholesterol levels from day 30 and day 50, as well as statistically significant different from the negative control, and can affect the index spleen and pancreas but does not affect the index of the kidneys, liver, heart, and lungs.